2020
DOI: 10.3390/cells9040943
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ascorbic Acid Ameliorates Oxidative Stress-Induced Corneal Endothelial Damage via Suppression of Apoptosis and Autophagic Flux Blockage

Abstract: Compromised pumping function of the corneal endothelium, due to loss of endothelial cells, results in corneal edema and subsequent visual problems. Clinically and experimentally, oxidative stress may cause corneal endothelial decompensation after phacoemulsification. Additionally, in vitro and animal studies have demonstrated the protective effects of intraoperative infusion of ascorbic acid (AA). Here, we established a paraquat-induced cell damage model, in which paraquat induced reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…18,19 In addition, several in vitro studies have also shown that antioxidants can promote CEC proliferation and prevent apoptosis. [20][21][22] Despite this body of knowledge, there have not been any clinical studies directly showing the relationship between ECD and aqueous humor antioxidants.…”
Section: Undesirable Ecd Declinementioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In addition, several in vitro studies have also shown that antioxidants can promote CEC proliferation and prevent apoptosis. [20][21][22] Despite this body of knowledge, there have not been any clinical studies directly showing the relationship between ECD and aqueous humor antioxidants.…”
Section: Undesirable Ecd Declinementioning
confidence: 99%
“…On the other hand, it has recently been reported that taking antioxidant supplements before or during the phacoemulsification process of cataract surgery can protect CEC from free radical damage 18,19 . In addition, several in vitro studies have also shown that antioxidants can promote CEC proliferation and prevent apoptosis 20‐22 . Despite this body of knowledge, there have not been any clinical studies directly showing the relationship between ECD and aqueous humor antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the prophylactical application of topical AA can improve phacoemulsification-induced oxidative stress and loss of human CECs [219]. Furthermore, it also has been shown that oxidative stress-induced cell autophagy and apoptosis can be reversed by AA pretreatment [26].…”
Section: Natural Antioxidant Therapy For Oxidative Stress-related Eye...mentioning
confidence: 78%
“…Lipidated microtubule-associated protein light chain 3 (LC3-II; an autophagosome membrane-bound protein) assists in autophagosome formation, and sequestosome 1 (p62/SQSTM1) binds to LC3-II to assist in autophagosome and lysosome fusion and the formation of autolysosomes to remove abnormal proteins and organelles; this process is called autophagic flux [24]. Severe oxidative stress damage can block autophagic flux, leading to the inability of autophagosomes to bind to lysosomes, resulting in p62 accumulation [25,26]. p62 accumulation induces apoptosis through the activation of caspase-8 [27].…”
Section: Molecular Aspects Of Oxidative Stress-induced Cell Damagementioning
confidence: 99%
See 1 more Smart Citation